2007
DOI: 10.4490/algae.2007.22.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Total RNA from a Freshwater Green Alga, Zygnema cruciatum, Containing High Levels of Pigments

Abstract: Conventional methods for the isolation and purification of mRNA from Zygnema were unsuccessful because of its high amount of pigments and RNA interactive molecules. In particular, pigments were difficult to remove using conventional protocols because they interacted with RNA during pulverization of the materials. This resulted in total degeneration of RNA in two to three hours. To alleviate this problem, we developed an isolation method that utilized DEAE-cellulose resin. The pigments bound to DEAE anion excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…While phenolics are less common in non‐streptophycean green algae, in Zygnematophyceae they have been repeatedly reported (Han et al. , Remias et al. ,b, Pichrtová et al.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While phenolics are less common in non‐streptophycean green algae, in Zygnematophyceae they have been repeatedly reported (Han et al. , Remias et al. ,b, Pichrtová et al.…”
Section: Discussionmentioning
confidence: 98%
“…Other abiotic stresses such as desiccation and temperature fluctuations could also be responsible for increasing the content of phenolics, due to their high-antioxidative potential. While phenolics are less common in non-streptophycean green algae, in Zygnematophyceae they have been repeatedly reported (Han et al 2007, Remias et al 2012a,b, Pichrtov a et al 2013.…”
Section: Discussionmentioning
confidence: 98%
“…Pinkish vacuoles are also known from Mesotaenium macrococcum (Ettl & Gärtner, 1995). The tannin-like precipitation capability of phenols from Zygnema cruciatum was depicted by Han et al (2007), who reported that the pigments effectively interact with RNA during grinding, thus denaturising not only proteins but also nucleotides, despite using established extraction protocols. The tannin-like precipitation capability of phenols from Zygnema cruciatum was depicted by Han et al (2007), who reported that the pigments effectively interact with RNA during grinding, thus denaturising not only proteins but also nucleotides, despite using established extraction protocols.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, these compounds have been found in members of the Zygnematophyceae [12, 60], which might be explained by their close relationship to land plants [6, 77]. In addition, a high amount of uncharacterised pigments was detected when attempting to isolate RNA from Z. cruciatum [22]. It could be speculated that these pigments were also phenolics, but there are many other compounds in the aqueous phase.…”
Section: Discussionmentioning
confidence: 99%
“…The UV-screening ability of phenolic substances found in some members of the class Zygnematophyceae has already been discussed [18, 60]. Moreover, high amounts of water-soluble pigments, probably also phenolics, have been reported to occur in Zygnema cruciatum [22], but their role in UV screening has not been tested. In this study, we examined if the production of phenolics in Zygnema is enhanced by experimental UV exposure.…”
Section: Introductionmentioning
confidence: 99%